The Role of Instructional Critical Thinking Skills Training Programs on Improving Teaching Practicability: EFL Teachers Perspectives - Hassoun, Zeinab Isam Ahmed (Advances in Social Sciences Research Journal, 2019)
This research paper is conducted to explore Sudanese EFL teachers’ stand points on the role and effect of instructional critical thinking training programs in terms of developing EFL teaching practices. Another aim of my research paper was that brought together two factors; language teaching theories and critical language awareness theory. Thus, the research paper tried to prepare Sudanese teachers to be aware of developing students’ cognitive and meta-cognitive skills based on scheduled teachers’ training programs. This would be highlighted in the critical language awareness theory and therefore the teacher would play a significant role in engaging learners in successful interaction, through creating participation opportunities based on the notion of critical thinking. The main contribution of this research paper is a framework for infusing critical thinking pedagogy across courses in English language skills that are taught to undergraduate students in Sudanese universities in general and Mamoon Humaida University in particular. Then it urges authorities, administrations and decision makers in Ministry of Higher Education to prepare teachers in order to emphasize processes through which critical thinking pedagogy can foster learning that leads to language learning development. . As for quantitative data, a descriptive method has been adopted to conduct this research paper. The required data were collected through questionnaire which was tried out on 50 English language staff teachers at Mamoon Humaida University in Sudan. The questionnaire was made to identify in-service teachers’ views on the role of critical thinking skills in Sudanese EFL pedagogy and their attitude towards training programs of practical teaching development with regard to critical thinking skills implementation. The obtained information was analyzed by using (SPSS) program and then the researcher provided the required interpretation for the tabulated data. The research paper findings revealed that most of Sudanese EFL teachers (subjects of this research paper) are enthusiastic to be enrolled ib training programs related to the implementation of critical thinking skills in EFL classes. The majority of teachers agreed that critical thinking skills can be considered as one of the factors that instill language learning process. They also emphasize the effectiveness of new strategies compared with the poor effect of the adopted classic methods of teaching in terms of reflecting up to date knowledge. As they consider critical thinking skills as an innovative method enable EFL learners to evaluate the learning process and reinforce learning autonomy. Most of participants’ responses showed their interest to improve teaching performance by adopting critical thinking and that would be fruitful when it is facilitated by administration supports. Since, critical thinking level would develop cognitive learning, however, traditional methods of teaching are no longer successful in EFL teaching and learning. The large number of respondents reflected the importance of on-going workshops about incorporating critical thinking in EFL teaching professional development. Also, seminars and webinar about the importance of high level of thinking are required to emphasize the success of EFL teaching of language skills. Most teachers ensured that a well trained in-service teacher of adopting critical thinking would improve learners’ language skills.